AN ANALYSIS OF THE STUDENTS’ ERROR ON CHANGING ACTIVE VOICE TO PASSIVE VOICE - Darohim, Mohammad (Universitas Islam Lamongan, 2020)
In passive voice, the subject receives the action of the verb. It is often used both in spoken and written form. For the learners, to change the active into passive voice of the target language is very confusing. The students usually make errors in building passive sentences as they ignore some aspects required in arranging best form of passive sentence. The students of El-Madani Islamic Boarding School Deket Lamongan were confused to change the verb in different tenses. The type of this research is descriptive quantitative. The research was chosen because this type of research defines what exist and may help to reveal new point and meaning. The survey and experiment, which were used in this research, was the phenomena of English errors passive sentences made by the students. The population of this research is all the students of El-Madani Modern Islamic Boarding School.The researcher used test and questionnaire to collect the data. The result of this study shows that (1) the kinds of errors commonly made by the students in changing active voice to passive voice are errors of omission, errors of addition, errors of miss-formation, and errors of miss-ordering (2) The students have difficulties in understanding passive voice especially in four tenses, simple present tense, simple past tense, present continuous tense and past continuous tense. (3) Factors which affect students’ ability in passive voice are: classroom atmosphere, lack of experience in using English, teacher’s explanation was not clear enough, the differences between passive voice in Bahasa and English. Keywords: Students’ errors, passive voice